Physical, chemical and microbiological qualities of dahi collected from Bogra and Mymensingh district of Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
The research work was carried out to evaluate the physical, chemical and microbiological qualities of dahi collected from different sources. In another step, cocci and rod ratio were investigated and microbial activities were also investigated by reactions in litmus milk. For this reason, dahi samples were collected from Bogra (Maharam Ali dahi-A, Rofat dahi-B, Jamuna Dahi-C) and Mymensingh district (Dayamoy-D, Misti Kanan-E, Krishna Kebin-F, BAU Dairy Farm Dahi-G, KR Market-H, Shes Moor-I). Physical tests were performed by a panel of expert judges. Chemical and microbiological parameters were tested in the Dairy Microbiology, Dairy Chemistry and Dairy Technology Laboratory of the Department of Dairy Science, Bangladesh Agricultural University, Mymensingh. In case of overall physical score, the highest value was (95.33±1.53) found in BAU Dairy Farm dahi. Considering chemical parameters, pH value and fat content of BAU Dairy Farm dahi were higher than that of other dahi samples. So, BAU Dairy Farm dahi was of the best quality on the basis of physical and chemical analysis. In microbiological analysis, (total viable count and coliform count) significant differences were found among all samples. All samples contained lower number of coliforms. No yeast and mold was found in any dahi sample may be followed the hygienic practices. Litmus milk characteristics of the isolated cultures showed desirable changes such as acid, smooth and firm coagulation obtained from Maharam Ali dahi and BAU Dairy Farm Dahi types of dahi sample which contained possible organisms of Streptococcus thermophilus and Lactobacillus bulgaricus. Considering all parameters, it can be concluded that BAU Dairy Farm dahi and Maharam Ali dahi were found as superior. In addition, this study gives information regarding the microbial status; e.g. cocci and rod ratio in the traditional fermented dahi of collected samples.Asian Australas. J. Biosci. Biotechnol. 2016, 1 (1), 134-140